Identification of Nursing Students' Anxiety and Readiness Facing Ners Competency Tests; Qualitative Study - Suzanna; Inne Yellisni; Gunawan Irianto; Arif Setyo Upoyo (Journal Of Nursing Practice, 2024)
Background: Having a  registration  certificate (STR) a  nurse  must  take  a  competency  test  as  a  condition for ownership of  the  STR.  For nursing  students,  competency  tests  are  a  big  challenge and complex,  so  special  preparation  and  attention  are  needed  for  students  and universities. The implementation of the competency test can create feelings of concern, fear, tension, and anxiety for fear of not  passing  the  competency  test. The problem about low graduation rate for ners competency test is influenced by several factors. One of internal factor consist of anxiety and fear facing ners competency test. Purpose: This study identified the perception and experience anxienty dan readiness of few nursing students facing competency test. Method: The study design is qualitative and study was conducted using semi-structured interview. Recruitment of partisipants for the interview was based on purposive sampling methods. Interview were conducted with a maximum 14 participants with saturation data. Analiysis in this study with content analysis. Results: This study explored the perception and experience anxienty dan readiness of few nursing students facing competency test. The current study identified four themes : deep feeling of fear, extreme anxiety, unpreparedness within, surrender and pray. Conclusion: The feelings of anxiety, fear and worry felt by students whether they are taking an exam for the first time or those who are repeating it. In fact, this feeling has quite an impact on the psychological condition, which is also compounded by the student's unpreparedness facing ners competency test.